Legal Position for Implementing Credit Provisions without Written Agreement at the Transmission Employees - Farik Farik; Dahniarti Hasana; Ira Alia Maerani (Sultan Agung Notary Law Review, 2022)
This study aims to determine and analyze thethe legal position of implementing credit without a written agreement at the Transmission and Substation Employee Cooperatives in Kudus City, as well as to know and analyze aboutlegal protection for creditors who provide credit without an agreement to debtors at the Transmission and Substation employee Cooperatives in Kudus City who are in default. This research method uses an empirical juridical approach, namely legal research that uses secondary data as initial data, which is then followed by primary data in the field or on the community. Based on the results of the study concluded: 1)The legal position of the implementation of granting credit without a written agreement at the Transmission and Substation Employee Cooperatives in Kudus City is legal according to the perspective of civil law because it has been carried out in accordance with the terms of the validity of the agreement as referred to in Article 1320 of the Civil Code, namely agree to bind himself, the ability to make an agreement, a certain thing and a lawful cause. Credit agreement without a written agreement made by the Cooperative Employee Substation Transmission of Kudus City has met all of these conditions. ManagerKudus City Transmission and Substation Employees Cooperativein carrying out its activities, it is also in accordance with the provisions of Act No. 25 of 1992 concerning Cooperatives, andlegal certainty has been fulfilled as the theory of legal certainty presented Gustav Radbruch who stated that legal certainty is certainty about the law itself; 2) Legal protection for creditors against debtor defaults on the implementation of unwritten agreements at the Kudus City Transmission and Substation Employee Cooperatives has been carried out properly, namely by conducting deliberation and/or mediation (non-litigation) efforts aimed at creating an agreement to disburse members' money. The exist in cooperatives that are sourced from principal savings, mandatory savings, and voluntary savings belonging to the member who is in default. Another form of legal protection that has also been carried out by the Management of the Transmission and Substation Employees Cooperatives in Kudus City is in terms of paying monthly installments from members, it is carried out by auto-debit to the bank account belonging to the member concerned.